2013
DOI: 10.2478/s11756-013-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening antibacterial activity of entomopathogenic bacteria isolated from pests of hazelnut

Abstract: Thirty-seven entomopathogenic bacteria isolated from six common pests of hazelnut in the Black Sea Region of Turkey have been screened for their potential of antibacterial substance production against indicator bacteria by the agar spot assay and well diffusion assay. Results indicated that 13.5% of entomopathogenic bacteria, Pseudomonas fluorescens (Pf-Xd1), Bacillus polymyxa (Bp-Ar2), Bacillus thuringiensis (Bt-Bn1), Serratia marcescens (Sm-Mm3) and Pseudomonas flourescens (Pf-Aa4) isolated from pests of Xyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In a previous study, high antibacterial activity of Sm-Mm3 was determined against several indicator microorganisms by well diffusion assay (Ugras et al, 2013). Results of this study demonstrated that the antibacterial substance was active against several bacteria, including Bacillus thuringiensis strains, B. cereus, B. polymyxa, B. subtilis, Enterobacter sp., Enterococcus faecalis, Erwinia amylovora, Proteus mirabilis, Paucimonas lemoignei, Pseudomonas fluorescens, P. syringae, Staphylococcus cohni, S. epidermidis, and Xanthomonas axonopodis.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…In a previous study, high antibacterial activity of Sm-Mm3 was determined against several indicator microorganisms by well diffusion assay (Ugras et al, 2013). Results of this study demonstrated that the antibacterial substance was active against several bacteria, including Bacillus thuringiensis strains, B. cereus, B. polymyxa, B. subtilis, Enterobacter sp., Enterococcus faecalis, Erwinia amylovora, Proteus mirabilis, Paucimonas lemoignei, Pseudomonas fluorescens, P. syringae, Staphylococcus cohni, S. epidermidis, and Xanthomonas axonopodis.…”
Section: Resultsmentioning
confidence: 81%
“…In a previous study, high antibacterial activity of Sm-Mm3 was determined against several indicator microorganisms by well diffusion assay (Ugras et al, 2013 (Ugras et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations